PELATIHAN BERPIDATO BAHASA INGGRIS PADA MAHASISWI DI AKADEMI KEBIDANAN BARUNA HUSADA SIBUHUAN - Harahap, Yulina Oktaviani (Universitas Aufa Royhan Di Kota Padangsidipuan, 2023)
Speaking is a crucial component of language proficiency that students need to possess in order to be able to communicate in English. One of the approach to improve their English-speaking skills, boost their self-esteem, exchange ideas, and express themselves to an audience in speech. The descriptive study's analysis of students' speaking capabilities was its main objective. During a speech at Akbid Baruna Husada academic year 2022/2023. Ten students who were chosen at random to participate in the study. The information was gathered through a speaking exam in which the students were required to present a speech that had been assessed based on speeches from [1] and [2], and included (a) organizing speech; (1) Introduction, (2) Body; primary theme; and supporting evidence, a connecting sentence, (3). Conclusion; mark the conclusion; vocal variation and pauses; reinforcement); (b) the speech's phrasing; (1) Word choice, (2) grammar. giving a speech; (1); and (c). Body language, eye contact, and facial expressions of the speaker movement. (2).Speaker articulation, pronunciation, and voice. The student's speaking skill in speech was classified as